PENGARUH KEGIATAN ART CRAFT MELUKIS BEBAS TERHADAP KREATIVITAS ANAK USIA 4-5 TAHUN DI RA PERWANIDA 3 KOTA PALEMBANG - Puspita Sari, Agnes; Febriyanti; Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of children's creativity in art activities is caused by the lack of stimulation and variety in interesting learning activities. The purpose of this study is to determine the influence of free painting art craft activities on the creativity of children aged 4-5 years in RA Perwanida 3 Palembang City. This study uses one class with an experimental group. This type of research is Pre-Experimental Design. With a quantitative research approach and One Grub Pretest Postest Design. The sample in this study amounted to 13 children aged 4-5 years at RA Perwanida 3 Palembang City. The data collection technique used observation, documentation and tests. The data analysis technique used validity, normality, reliability, homogeneity and hypothesis tests. From the results of the calculation, a calculation of 10.676 and ttable = 2.179 were obtained where there was a significant difference in children before and after receiving treatment. And from the results of the t-test, a sig value of 0.001 was obtained with the criterion <0.05 So it can be said that there is an influence of free painting art craft activities on children's creativity. Keywords: Art Craft, Painting, Creativity.